Analisis Pengaruh Knowledge, Work Training, Risk Behavior dan Use of Personal Protective Equipment terhadap Loading and Discharging Work Safety - Dedy Rusmiyanto; Muhamad Abdul Ghofur (STIE Widya Manggala, 2020)
This study aims to determine the effect of knowledge, work training, risk behavior, and use of personal protective equipment on loading and discharging work safety. The population in this study were all loading and unloading labor at Tanjung Emas Port Semarang with a sample of 100 respondents. The sampling technique used is probability sampling The analytical method used is quantitative analysis, the data were analyzed using multiple linear regression The results of multiple linear regression analysis obtained the equation Y = -2.004 + 0.286 X1 + 0.246 X2 + 0.253 X3 + 0.328 X4 + μ. And the coefficient of determination is 62.3%, it means all independent variables can explain the dependent variables as much as 62.3% while the rest (100% - 62.3% = 37.7%) is explained by other variables outside the regression model.